Neuroendocrine differentiation of prostate cancer: A literature review (2014)
Prostate cancer is the most common solid neoplasia in the male population. Due to the rise in life expectancy and the screening with prostate antigen, the incidence of this tumor has increased in developed nations as well as in countries with poor resources. Nevertheless, the natural history of the disease varies greatly and is difficult to predict, since there is discrepancy between the new cases and the mortality rate. A better understanding of the biological behavior of this tumor is required. The neuroendocrine differentiation has received great attention in the last few years, due to its prognostic and therapeutic yield, as well as because it demonstrates the clinical progression of disease in spite of conventional treatment. With this review, an attempt is made to define the neuroendocrine differentiation in prostate cancer. © 2014 Sociedad Colombiana de Urología.